DELIVERY OF AN ALIVE FOETUS THROUGH CAESAREAN SECTION IN A CASE OF DECLARED MATERNAL DEATH - Nisa, Rahat -un-; Bashir, Rubina; ullah, Hizb (Journal of Ayub Medical College Abbottabad, 1998)
A 25 years old multipara having full term pregnancy was being treated at Civil Hospital Haripur, for septic meningitis while she suddenly went into cardiac arrest. Resuscitation was started immediately by intubation, ventilation and external cardiac massage and the patient was shifted to CCU of DHQ (Teaching) Hospital, Abbottabad, where she was declared dead however Fetal Heart Sound (FHS) was still audible at a rate of 40/min. She was shifted to Women and Children Hospital, Abbottabad for further management of the foetus while keeping the dead body on positive pressure ventilation (total duration of transfer time was not less than 44 minutes). The obstetrician found no heart sounds and fixed dilated pupils in the mother while the FHS were present at a rate of 35/min. Decision to carry out postmartal Csection was made. An alive baby with apgor score of 1/10 was delivered through midline lower abdominal incision of abdominal wall and a vertical uterine incision in a bloodless field. While suturing the incisions, bleeding started from the wounds and a hectic effort was, than, made to resuscitate the patient. Her heart rhythm came back and it started beating at a steady rate of 80/min while her systolic blood pressure was raised to 80 mm Hg. However, she still remained deeply comatose and without sings of spontaneous respiration. She eventually died 48 hours later. Foetus was resuscitated successfully and on follow up remains healthy and without any neurological deficit.